The Relationship Between Teacher Exemplary Behavior and the Character of Fifth Grade Students at Sepanjang Jaya IV Public Elementary School - Santi Sahtun Sahwal; Yohamintin Yohamintin (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study was conducted to examine the relationship between teachers’ exemplary attitudes and the character development of fifth-grade students at Sepanjang Jaya IV Public Elementary School. Methodology: This study employed a quantitative method with a correlational approach. The sample consisted of 56 students selected using purposive sampling. Data were collected using a Likert scale and analyzed through the Pearson Product Moment correlation test with the assistance of SPSS software version 21. Main Findings: The research findings revealed a relationship between teacher role modeling and the character of fifth-grade students. The stronger the role modeling demonstrated by the teacher, the more positive the character development in the students. Novelty/Originality of this study: This study presents a novel element by specifically examining the relationship between teacher role modeling and character development in fifth-grade elementary school students, who are at a developmental stage where the teacher figure has significant influence. Furthermore, this research highlights the concrete forms of teacher role modeling that align with the conditions of the elementary school environment and analyzes them through an approach that directly examines the relationship between variables. Thus, this study provides an important contribution to the development of character education in elementary schools, especially in the implementation of teacher role modeling values in daily practice.